(Table 1) Interstitial-water chemistry at DSP Leg 58 Holes - Gieskes, Joris M; Johnson, Jeff (Supplement to: Gieskes, JM; Johnson, J (1981): Interstitial-water studies, Leg 58. In: Larson, RL; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 61, 607-611, https://doi.org/10.2973/dsdp.proc.61.117.1981, 1981)
Interstitial waters from several sites drilled during Leg 58 have been analyzed for major constituents. Data for Sites 442, 443, and 444 in Shikoku Basin indicate that only small changes occur in the chemical composition. We did not note any influence on the interstitial water chemistry resulting from reactions taking place in the underlying basalts. Site 445 data indicate that reactions must occur in the sediment column, leading to decreases in dissolved magnesium and increases in dissolved calcium. In addition, a source of dissolved calcium appears in the underlying basalts. At Site 446, changes appear in dissolved-calcium and -magnesium concentrations, resulting mainly from alteration reactions in the basalts. Dissolved potassium has its main sink in deeper-lying sediments or basalts. Changes in dissolved strontium at Sites 445 and 446 can be explained in terms of carbonate recrystallization. At all sites, changes in dissolved manganese and lithium appear to be related to the presence of biogenic silica in the sediments.